“Death as the One Great Certainty”: ethical implications of children with irreversible cardiorespiratory failure and dependence on extracorporeal membrane oxygenation - Moynihan, Katie M.; Taylor, Lisa S.; Siegel, Bryan; Nassar, Natasha; Lelkes, Efrat; Morrison, Wynne (Frontiers in Pediatrics, 2024)
Introduction: Advances in medical technology have led to both clinical and philosophical challenges in defining death. Highly publicized cases have occurred when families or communities challenge a determination of death by the irreversible cessation of neurologic function (brain death). Parallels can be drawn in cases where an irreversible cessation of cardiopulmonary function exists, in which cases patients are supported by extracorporeal cardiopulmonary support, such as extracorporeal membrane oxygenation (ECMO). Analysis: Two cases and an ethical analysis are presented which compare and contrast contested neurologic determinations of death and refusal to accept the irreversibility of an imminent death by cardiopulmonary standards. Ambiguities in the Uniform Determination of Death Act are highlighted, as it can be clear, when supported by ECMO, that a patient could have suffered the irreversible cessation of cardiopulmonary function yet still be alive (e.g. responsive and interactive). Parallel challenges with communication with families around the limits of medical technology are discussed. Discussion: Cases that lead to conflict around the removal of technology considered not clinically beneficial are likely to increase. Reframing our goals when death is inevitable is important for both families and the medical team. Building relationships and trust between all parties will help families and teams navigate these situations. All parties may require support for moral distress. Suggested approaches are discussed.